Meat Food Group Intakes and the Risk of Type 2 Diabetes Incidence - Hosseini-Esfahani, Firoozeh; Beheshti, Niloofar; Koochakpoor, Glareh; Mirmiran, Parvin; Azizi, Fereidoun (Frontiers in Nutrition, 2022)
Background and Aims: This study aimed to evaluate the association of meats and their substitute food group intakes, including nuts, eggs, and legumes, with type 2 diabetes (T2D). Methods: For this secondary analysis, we selected eligible adults (n=6112) from the Tehran Lipid and Glucose Study participants with a median follow-up of 6.63 years. Expert nutritionists assessed dietary intakes using a valid and reliable semi-quantitative food frequency questionnaire. Biochemical and anthropometric variables were assessed at baseline and follow-up examinations. We used multivariable Cox proportional hazard regression models to estimate the new onset of T2D concerning meats and their substitute food groups. Results: We performed this study on 2749 men and 3363 women, aged 41.4±14.2 and 39.1±13.1 years, respectively. The number of participants with incident T2D was 549. After adjusting for confounders, legume [HR: 1, 0.74 (0.58-0.94), 0.69 (0.54-0.90), 0.65 (0.50-0.84), P trend=0.01)] was inversely associated with incident T2D. Fish intake [HR: 1, 1.0 (0.79-1.27), 1.17 (0.91-1.50), 1.14 (0.89-1.45), P trend=0.01)] was positively associated with incident T2D. In subjects who reported poultry consumption of 36.4-72.8 grams/day, a positive association [HR:1.33 (1.03-1.71)] between poultry intake and T2D risk was observed. Conclusion: Our findings revealed that a diet rich in legumes significantly reduced the risk of T2D incidence, while a diet high in poultry increased the risk of T2D incidence, probably due to high-temperature cooking methods and environmental contaminants.